Effectiveness of the using powder coating for protection of metal construction - Lastivka, Oles (Transfer of innovative technologies, 2023)
Сurrent state of the Ukrainian economy causes to resolve a range of questions related to the improvement of production and increase in the ecological safety of products, including paint-and-varnishes materials, in combination with ensuring high operational properties of coatings based on them. This questions can be solved by scaling up production using eco-friendly powder coating. The increase in popularity of powder coatings can be explained by their environmental adequacy and attractiveness from the perspective of the environmental protection as well as high effectiveness related to the possibility of obtaining high quality protective and decorative coatings with the high corrosion and chemical resistance as well as controllable physical and mechanical and dielectric characteristics during the one-layer application. The analysis of research results shows that the effectiveness of use of metakaolin and talc as fillers in the powder coating increases in proportion to their content in the system. The optimal area of the powder coating with metakaolin and talc is limited to the additive in the range of 20 to 30 % and polyester resin in the range of 55 to 65 %. Using the mentioned range of fillers in the powder coating contributes to the decrease in the peeling width and metal corrosion width and places the coating into atmospheric corrosivity categories С3 and С4 according to ІSO 12944-2:2017 having a high (Н) lifespan from 15 to 25 years in accordance with DSTU ISO 12944-1 In this case, one of the most common methods of influence on properties of paint-and-varnishes coatings is to create polymer composites by combining polyester raw materials with inorganic fillers.